2003
DOI: 10.1002/jmv.10312
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of simian varicella virus

Abstract: Simian varicella virus (SVV) is closely related to varicella-zoster virus (VZV) and induces a natural varicella-like disease in nonhuman primates. Therefore, simian varicella is a useful model to investigate varicella pathogenesis and to evaluate antiviral therapies. In this report, we review recent studies on SVV pathogenesis and latency. Experimental infection of African green monkeys is followed by a 7-10 day incubation period during which a viremia disseminates the virus throughout the body. Clinical disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…A second, more pronounced viremia occurs between 10 and 21 days after infection. Infection of susceptible nonhuman primates, such as African green monkeys with simian varicella virus (SVV), induces a transient viremia peaking 7 to 10 days following experimental intratracheal inoculation (12). As such, we focused our attempts to detect virus within the first 28 days following experimental inoculation by assessing both mucosal and systemic sites.…”
Section: Discussionmentioning
confidence: 99%
“…A second, more pronounced viremia occurs between 10 and 21 days after infection. Infection of susceptible nonhuman primates, such as African green monkeys with simian varicella virus (SVV), induces a transient viremia peaking 7 to 10 days following experimental intratracheal inoculation (12). As such, we focused our attempts to detect virus within the first 28 days following experimental inoculation by assessing both mucosal and systemic sites.…”
Section: Discussionmentioning
confidence: 99%
“…Simian varicella virus (SVV) is a neurotropic alphaherpesvirus that naturally infects non-human primates (NHP) and shares 75% DNA homology and genome colinearity with VZV [41], [42], [43]. The exact mode of SVV transmission has not yet been experimentally determined but it is believed to occur through contact with skin lesions of an infected animal, or via exposure to virus-laden aerosolized droplets from infected animal(s), as described for VZV transmission in humans [44], [45]. We have recently shown that intrabronchial infection of rhesus macaques (RM) with SVV recapitulates the hallmarks of acute VZV infection in humans: (1) generalized varicella rash; (2) development of cellular and humoral responses; (3) resolution of acute infection; and (4) establishment of latency in sensory ganglia [46].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis and clinical features of simian and human varicella are comparable (13,20). Following resolution of primary disease, SVV and VZV establish latent infections within neurons of the neural ganglia and may subsequently reactivate to cause a secondary disease, such as herpes zoster (13,22,26,30).…”
mentioning
confidence: 99%